(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
To address the circulating current and uneven power distribution issues in multi-virtual synchronous generator (VSG) parallel systems caused by incon sistent line impedances, an improved control strategy introducing dynamic vir tual impedance is proposed. By analyzing the active power-frequency and reac tive power-voltage control characteristics of VSG, the influence mechanism of line impedance differences on power distribution accuracy and circulating cur rent is revealed. In the proposed strategy, adaptive virtual impedance is intro duced to enhance the inductive feature of the output impedance, achieving power decoupling, and a voltage feedback integral link is combined to compensate for the voltage drop caused by virtual impedance. Simulation results show that this strategy can effectively suppress the circulating current between parallel VSGs, achieve precise sharing of active and reactive power, and improve system stabil ity and power quality.